Terapi Digital Virtual Reality terhadap Kecemasan pada Pasien Kanker yang Menjalani Kemoterapi - Isran, Isran; Mahdi, Andi Nurhikma; Israyana, Israyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of Virtual Reality digital therapy on anxiety in cancer patients undergoing chemotherapy. The research method used a pre-experimental design with a one-group pre-test and post-test approach. The results showed a decrease in anxiety scores with an average difference (post-pre) of 10.267. The Paired Sample t-Test yielded a t-value of 0.785, df = 29, and a significance value (p-value) of 0.000 (p < 0.05), which means that there is a significant effect of VR digital therapy on reducing anxiety in cancer patients undergoing chemotherapy. In conclusion, Virtual Reality digital therapy is effective in reducing anxiety in cancer patients undergoing chemotherapy. This intervention can be used as a non-pharmacological complementary therapy to support the psychological care of cancer patients. Keywords: Anxiety, Cancer, Chemotherapy, Virtual Reality